2019
DOI: 10.56454/ycur2379
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Irrigation Timing on Tarnished Plant Bug Populations and Yield of Cotton

Abstract: The tarnished plant bug, Lygus lineolaris (Palisot de Beauvois), is the most significant insect pest of cotton, Gossypium hirsutum (L.), in the mid-southern United States (Arkansas, Louisiana, Mississippi, Missouri, and Tennessee). Past research has shown the impact that planting date, nitrogen rate, and variety selection has on tarnished plant bug populations, but a paucity of data exists on the effect irrigation timing has on tarnished plant bug. Experiments were conducted at the Mississippi State University… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Various cotton and landscape management practices can reduce reliance on insecticides for tarnished plant bug control. Previous research has shown that planting early, using early maturing cultivars (Adams et al, 2013), optimizing nitrogen use rates (Samples et al, 2019), delaying irrigation until after bloom (Wood et al, 2019), and managing winter annuals (Snodgrass et al, 1984(Snodgrass et al, , 2005(Snodgrass et al, , 2006 can reduce tarnished plant bug populations. In general, these management practices have the potential to reduce pre-bloom infestation levels.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Various cotton and landscape management practices can reduce reliance on insecticides for tarnished plant bug control. Previous research has shown that planting early, using early maturing cultivars (Adams et al, 2013), optimizing nitrogen use rates (Samples et al, 2019), delaying irrigation until after bloom (Wood et al, 2019), and managing winter annuals (Snodgrass et al, 1984(Snodgrass et al, , 2005(Snodgrass et al, , 2006 can reduce tarnished plant bug populations. In general, these management practices have the potential to reduce pre-bloom infestation levels.…”
mentioning
confidence: 99%
“…In general, these management practices have the potential to reduce pre-bloom infestation levels. When these practices are coupled with sound integrated pest-management strategies of rotating chemistries, following action thresholds, and using best insecticide tank mixes, growers have a chance to reduce the total number of insecticide applications for adequate control in a growing season (Adams et al, 2013;Samples et al, 2019;Snodgrass et al, 1984Snodgrass et al, , 2005Snodgrass et al, , 2006Wood et al, 2019).…”
mentioning
confidence: 99%